Condom Breakage Among Young Black Men Who Have Sex With Men: An In-Depth Investigation Including Men Living With HIV/AIDS. Issue 2 (February 2016) - Crosby, Richard A.; Mena, Leandro
Abstract : Abstract: Correlates of condom breakage (reported by 19% of 398 young black who have sex with men) for anal insertive sex included the following: condoms drying out ( P = 0.018), erection loss during application ( P = 0.03), and using erection-enhancing drugs ( P = 0.003). Breakage was 2.7 times greater for HIV-positive men ( P = 0.001). Breakage was associated with testing positive for urethral infections ( P = 0.012). Abstract : This study of condom breakage (reported by 19% of 398 young black men who have sex with men) found that breakage was 2.7 times greater for HIV-positive men. Breakage was also associated with urethral infections.